Information Literacy among High School Students: A Study about Cyber Literacy for the use of Online Resources - Sunil, M. V.; G. Srilakshminarayana (Journal of Information and Knowledge, 2022)
Post-COVID situations have opened many opportunities and challenges in the education world. The challenges are the accumulation of the pre-COVID and the COVID technology requirements to have a proper environment for the students. The recently released National Crime Records Bureau (NCRB) of India cautioned the information and library professionals about the need for information literacy programs regarding the use of Online Resources. In response, this study was attempted among students of select high schools in Mysore city to understand the literacy level regarding cyber security and its implication. The data analysis suggests the urgent need for an information literacy program for teachers and librarians.